Feasibility of Monte Carlo simulation for predicting deformation modulus of rock mass. (July 2019) - Fattahi, Hadi; Varmazyari, Zahra; Babanouri, Nima
Abstract: Deformability of rock mass significantly influences its behavior and is, therefore, an important consideration for the design of underground structures. The deformation modulus of rock mass (Em ) is directly measured from the time-consuming and expensive uniaxial jacking tests, whose results often have a large scatter. Hence, in this study, an attempt has been made to evaluate Em in different conditions using the Monte Carlo simulation (MCS). To achieve this aim, the most important parameters influencing Em were investigated. The parameters of rock mass rating (RMR), depth, uniaxial compressive strength of intact rock (UCS), and elastic modulus of intact rock (Ei ) were selected as the model inputs. First, an equation was developed by the multiple non-linear regression (MNLR), and it was then used for evaluation and prediction of Em by the MCS technique. The results indicated that this approach is capable of simulating Em ranges with a good level of accuracy. The mean of the MCS-simulated values of Em was obtained as 15.13 GPa, while the measured values of Em had a mean equal to 14.54 GPa. Moreover, the results of a sensitivity analysis demonstrated that the deformation modulus of the intact rock (Ei ), among the other parameters, is of the most influence on Em .